Developments toward hard X-ray radiography on heavy-ion heated dense plasmas. (28th October 2014) - Li, K.; Borm, B.; Hug, F.; Khaghani, D.; Löher, B.; Savran, D.; Tahir, N. A.; Neumayer, P.
Abstract: We have studied the potential of hard X-ray radiography as a diagnostic in high energy density experiments, proposed for the future Facility for Antiproton and Ion Research (FAIR). We present synthetic radiographic images generated from hydrodynamic simulations of the target evolution. The results suggest that high-resolution density measurements can be obtained from powerful hard X-ray sources driven by a PW-class high-energy laser system. Test measurements of a prototype hard X-ray imaging detector for photon energies above 100 keV are presented.